The Influence of Social Media Marketing on Purchase Decision Mediated by Brand Awareness and e-WOM - Nina Lestari; Nina Nurhasanah (International Journal of Economics (IJEC), 2025)
This study analyzes the influence of social media marketing on brand awareness, electronic word of mouth (e-WOM), and consumer purchase decision for Tyeso Tumbler products in Jakarta. The research method used is quantitative with purposive sampling technique through questionnaires to 110 respondents, and data analysis using Structural Equation Modeling (SEM). The results of the study indicate that social media marketing has a positive and significant effect on brand awareness e-WOM, and purchase decision. In addition, brand awareness and e-WOM have a positive effect on purchase decision and are proven to act as mediating variables in the relationship between social media marketing and purchase decision. These findings confirm that professional social media management not only increases brand awareness but also encourages consumer interaction and strengthens purchase decision.